The Effect of Process Oriented Guided Inquiry learning on Achievement among Nursing Students in a Selected Private Institution of Higher Learning - Jeya Devi, Coomarasamy (2016)
New graduates from the diploma in nursing programme are found to lack the confidence and ability to make appropriate patient care decisions based on credible evidence, critical thinking and clinical reasoning. To be part of today’s healthcare environment, the students must learn not only these skills, but also be able to work as team members and as communicators of information for decision-making across interdisciplinary boundaries. These skills are difficult to impart through the current traditional teacher-centred methods. The primary purpose of this study was to determine whether Process Oriented Guided Inquiry Learning (POGIL), a constructivist-based instructional strategy introduced into a traditional teacher-centred environment would have an effect on the diploma in nursing students’ academic achievement and confidence in learning. In addition, the study explored the perception of the students towards POGIL as an instructional method. For the quantitative aspect of this mixed-methodological study, a quasi-experimental design was used to compare the achievement and confidence in learning scores between two groups of students who were in the final semester of the diploma in nursing programme (N=73). Statistically, there was no significant difference found in post-test scores and final school examination scores between the control (n=37) and experimental (n=36) groups although the mean scores were higher in the experimental group. The interactions between groups, gender and nationality in the post-test scores were also not significant. However, confidence in learning scores at the end of semester was statistically significant (p<.05) between the experimental and control group with the experimental group having a higher mean score. Qualitative data was gathered using a semi-structured interview format. The students perceived the learning environment created through the POGIL method as non-threatening and to have contributed to their self-confidence and motivation towards learning. In addition, they also stated that their skills in teamwork, communication, critical thinking and clinical reasoning had improved. Overall findings were extremely encouraging indicating that POGIL, as an instructional method has the potential to make a significant contribution to nursing education. Transversal competencies learned in a POGIL class would enable the nursing students to be “work ready” and adapt to the clinical environment with confidence.